Improving teacher performance through strengthening transformational leadership, pedagogical competence, and work ethic: a systematic literature review - Happy Gustin; Merry Lapasau; Widodo Widodo; Supardi Uki Sajiman (Jurnal Konseling dan Pendidikan, 2026)
This study systematically synthesized empirical evidence to examine the contribution of these factors to teacher performance. A Systematic Literature Review (SLR) following the PRISMA 2020 reporting guideline was conducted using peer-reviewed empirical studies retrieved from Google Scholar through Publish or Perish. After screening, eligibility assessment, and quality appraisal, 17 studies published between 2020 and 2026 met the inclusion criteria and were included in the qualitative synthesis. The findings indicate that most reviewed studies identified transformational leadership as the strongest organizational determinant of teacher performance by enhancing teacher motivation, organizational commitment, instructional innovation, and supportive school environments. Pedagogical competence improved instructional effectiveness through better lesson planning, classroom management, assessment, and student-centered learning, while work ethic strengthened teachers' professional responsibility, discipline, commitment, and instructional consistency. Overall, the synthesized evidence suggests that sustainable improvement in teacher performance requires integrated educational management strategies combining transformational leadership, continuous professional development, and supportive organizational cultures. These findings provide practical implications for school leaders and educational policymakers seeking to improve teacher performance and educational quality.